The Future of Physiologically Based Pharmacokinetic Modeling to Predict Drug Exposure in Pregnant Women. (6th March 2013) - Vinks, AA
Abstract : Pregnant women have long been orphaned from drug studies. The application of physiologically based pharmacokinetic modeling to quantitatively describe drug disposition and effects during pregnancy is an attractive approach that is now actively pursued as it allows optimal use of available information for both efficient study designs and prediction of maternal–fetal exposure. CPT: Pharmacometrics & Systems Pharmacology (2013) 2, e33; doi:10.1038/psp.2013.9 ; advance online publication 6 March 2013